Altered Coupling of Cerebral Blood Flow and Functional Connectivity Strength in First-Episode Schizophrenia Patients With Auditory Verbal Hallucinations - Chen, Jingli; Xue, Kangkang; Yang, Meng; Wang, Kefan; Xu, Yinhuan; Wen, Baohong; Cheng, Jingliang; Han, Shaoqiang; Wei, Yarui (Frontiers in Neuroscience, 2022)
Objective: Auditory verbal hallucinations (AVHs) are a major symptom of schizophrenia and are connected with impairments in auditory and speech-related networks. In schizophrenia with AVHs, alterations in resting-state cerebral blood flow (CBF) and functional connectivity have been described. However, the neurovascular coupling alterations specific to first-episode drug-naïve schizophrenia (FES) patients with AVHs remains unknown. Methods: Resting-state functional MRI and arterial spin labeling was performed on 46 first-episode drug-naïve schizophrenia (FES) patients with AVHs (AVH), 39 FES drug-naïve schizophrenia patients without AVHs (NAVH) and 48 healthy controls (HC). Then compare the correlation between the CBF and functional connection strength (FCS) of the entire gray matter between the three groups, as well as the CBF/FCS ratio of each voxel. Correlation analyses were performed between significant results between schizophrenia patients and clinical measures scale. Results: The CBF/FCS ratio was reduced in cognitive and emotional brain regions in both the AVH and NAVH groups, primarily in the crus I/II, vermis VI/VII, and cerebellum VI. In the AVH group compared to the HC group, the CBF/FCS ratio was higher in auditory perception and language processing areas, primarily the left superior and middle temporal gyrus (STG/MTG). The CBF/FCS ratio in the left STG and left MTG positively correlates with the score of the Auditory Hallucination Rating Scale in AVH patients. Conclusion: These findings point to the difference in neurovascular coupling failure between AVH and NAVH patients. And the dysfunction of the forward model based on the predictive and computing role of the cerebellum may increase the excitability in the auditory cortex, which may help to understand the neuropathological mechanism of AVHs.